The limits to Domestic Resource Mobilization in the Addis Ababa Action Agenda (AAAA) - Rodriguez Enriquez, Corina Maria (2015)
Although Domestic Resource Mobilization (DRM) has been highlighted as a key componentof the Addis Ababa Action Agenda (AAAA), the AAAA approach fails to recognizestructural barriers to developing countries? policy space and ability to mobilize resourcesin ways compatible with democracy, human rights compliance and gender equality.